(untitled) (Journal of Interdisciplinary Insights, 2024)
Innovation and entrepreneurship are increasingly vital for economic growth, necessitating quality education to equip students with critical skills. While industry collaboration is potentially valuable for fostering innovation and entrepreneurship education, integration strategies remain underexplored in China. This mixed-methods study examines optimal strategies for incorporating industry collaboration into curricula. Semi-structured interviews were conducted with 30 educators across 10 Chinese universities along with focus groups among 60 students. Additionally, 550 students and faculty completed questionnaires regarding their perceptions of industry engagement. Thematic analysis of qualitative data combined with descriptive statistics of surveys revealed internships, case studies, and guest lectures as preferred strategies, enabling technical skills development and mentorship. However, structural barriers like rigid administration, funding constraints, and conflicts of interest were identified. A comparative analysis finds that project-based programs yield greater knowledge transfer compared to ad-hoc activities. These findings inform institutional policies and curricular designs for enhanced innovation and entrepreneurship education through purposeful industry integration in the Chinese context.